2014
DOI: 10.1093/ntr/ntu170
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of AT-1001, an α3β4 Nicotinic Acetylcholine Receptor Ligand, at Human α3β4 and α4β2 nAChR

Abstract: Introduction: Genome-wide association studies linking the α3, β4, and α5 nicotinic acetylcholine receptor (nAChR) subunits to nicotine dependence suggest that α3β4* nAChR may be targets for smoking cessation pharmacotherapies. We previously reported that AT-1001, a selective α3β4* nAChR ligand binds with high affinity to rat α3β4 and human α3β4α5 nAChR, antagonizes epibatidine-induced activation of rat α3β4 nAChR in HEK cells and potently inhibits nicotine selfadministration in rats. Methods: Two-electrode vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Our results confirm earlier studies that AT-1001 binds with high affinity and selectivity to a3b4 nAChRs (Toll et al, 2012) and that it displays partial agonist activity (Zaveri et al, 2015). In HEK cells heterologously expressing the rat versions of the a3b4 and a4b2 nAChR subtypes, we found that AT-1001 displays 41-fold selectivity for the a3b4 subtype, which also is in general agreement with the initial report (Toll et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirm earlier studies that AT-1001 binds with high affinity and selectivity to a3b4 nAChRs (Toll et al, 2012) and that it displays partial agonist activity (Zaveri et al, 2015). In HEK cells heterologously expressing the rat versions of the a3b4 and a4b2 nAChR subtypes, we found that AT-1001 displays 41-fold selectivity for the a3b4 subtype, which also is in general agreement with the initial report (Toll et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…The difference between the efficacies found in these two types of assays may be related to receptor desensitization, which is more evident during the much longer stimulation period required in the 86 Rb 1 efflux assay than in patch-clamp measurements (see below). In our patch-clamp measurements of human a3b4 nAChRs expressed in HEK cells, AT-1001 displayed a potency of 0.4 mM, which is nearly identical to the potency found in a recent study in Xenopus oocytes expressing human a3b4 nAChRs (Zaveri et al, 2015). The potency of AT-1001 was 3.5-fold higher at the human than the rat a3b4 receptor in patchclamp measurements and 15-fold higher in 86 Rb 1 efflux assays.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…α4β2 insan beyninde en çok bulunan reseptör tipidir ve nikotin bağımlı-lığında anahtar rolü oluşturduğu düşünülmektedir. α4β2 agonisti olan vareniklin, sistisin, dianiklin gibi moleküller nAChR'lerini duyarsız hale getirir (2,8) . β2 alt ünite geni çıkarılan farelerin nikotin alma isteklerinin kaybolduğu, bu genin ventral tegmental alanda (VTA) tekrar sağlandığında nikotin aşermelerinin geri geldiği gösterilmiştir (9) .…”
Section: Nikotin Alımı Ve Nikotin Bağımlılığıunclassified